Down‐tail mass loss by plasmoids in Jupiter's and Saturn's magnetospheres. Issue 8 (19th August 2015) - Cowley, S. W. H.; Nichols, J. D.; Jackman, C. M.
Abstract Recent estimates of the plasma mass‐loss rates by the formation and down‐tail propagation of plasmoids observed in the plasma sheet in Jupiter's and Saturn's magnetosphere fall short of inner moon source rates by at least an order of magnitude. Here we argue that on the time scale between large‐scale disconnection events, ~15 h at Jupiter and ~45 h at Saturn, mass‐loaded closed flux tubes will typically have stretched out a few hundred planetary radii down tail at speeds ~100–200 km s−1. Consequently, the "plasmoids" of order ~10 planetary radii in length observed at closer planetary distances represent only a small planetward portion of the overall structure that is disconnected and lost down tail. Plasmoid mass‐loss estimates are then revised upward by around an order of magnitude, becoming comparable to the moon source values. Additional "hidden, " e.g., small‐scale, mass‐loss processes of comparable strength may not then be required. The essentially continuous azimuthally flowing source plasma in the dusk sector is shown to correspond to a plasma sheet layer adjacent to the magnetopause of width typically ~10% of the distance to the magnetopause in that local time sector. This physical picture also provides a simple explanation for the asymmetry in the plasmoid bipolar field signature observed at both Jupiter and Saturn and predicts that the apparent plasmoid length will increase with distance down tail to a limit beyond a few hundred planetary radii where the full ~100–200 planetary radii structures will be observed.